Theater for Expression (2020)
The project "Theater for Expression" is a pedagogical strategy that seeks to improve oral expression among interdisciplinary Cycle V students at Silvino Rodríguez School in Tunja, specifically at its Establecimiento Penitenciario Carcelario de Mediana Seguridad [Medium Security Penitentiary Institution] headquarters. This study is framed under a qualitative paradigm since it emphasizes the processes and decisions that students take. The study also focused on solving specific problems rather than contributing to scientific theory (Baez, 2003). Likewise, our current investigation was guided by critical-social research since it reflects on education and its current problems. We utilized an action research study mainly because the objective was to improve educational practices by means of creating strategies that could improve discourse and teaching. This study involved a group of students deprived of their freedom, who also worked in that context. In other words, the study took place in a space where the subjects and objects to be investigated, as well as the school and classroom are developed (Baez, 2003).